2006
DOI: 10.1590/s1516-89132006000500002
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and culture of soybean (Glycine max L. Merrill) microspores and pollen grains

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
0
2
0
1
Order By: Relevance
“…The Alexander stain showed the highest pollen viability (90.0-97.1%) which was likely an overestimated range in comparison to FCR (83.0%). The highest percentage of viability might be due to the fact that the stain killed the pollen (Parfitt & Ganeshan 1989;Kapyla 1991;Sedgly & Hardarb 1993;Khatum & Flowers 1995), and another drawback associated with these tests based on cellular content and presence of cellular content is that they do not guarantee that pollen is metabolically active or capable of growing pollen tubes (Rodrigues et al 2006). On the contrary, Auler et al (2006) used Alexander's stain in the medicinal species Baccharis trimera ('carqueja') and concluded that Alexander's stain was the best to estimate pollen viability.…”
Section: Discussionmentioning
confidence: 99%
“…The Alexander stain showed the highest pollen viability (90.0-97.1%) which was likely an overestimated range in comparison to FCR (83.0%). The highest percentage of viability might be due to the fact that the stain killed the pollen (Parfitt & Ganeshan 1989;Kapyla 1991;Sedgly & Hardarb 1993;Khatum & Flowers 1995), and another drawback associated with these tests based on cellular content and presence of cellular content is that they do not guarantee that pollen is metabolically active or capable of growing pollen tubes (Rodrigues et al 2006). On the contrary, Auler et al (2006) used Alexander's stain in the medicinal species Baccharis trimera ('carqueja') and concluded that Alexander's stain was the best to estimate pollen viability.…”
Section: Discussionmentioning
confidence: 99%
“…Fenomena di atas umumnya telah dilaporkan oleh banyak peneliti atau kelompok penelit pada berbagai tanaman budidya. Tanaman-tanaman dimaksud seperti tanaman tembakau (Volcov et al, 2005), Brassica (Zhang et al, 2006), kedelai (Rodrigues et al, 2006), tomat (Segui-Semarro dan Nuez, 2007), dan kentang (Panahandeh et al, 2008). Bagi tanaman jarak pagar, selain morfologi bunga berupa panjang dan lebar bunga, umur bunga juga menentukan frekuensi mikrospora uninukleat tengah dan akhir.…”
Section: E F Pembahasanunclassified
“…Soybean [ Glycine max (L.) Merrill, Fabaceae; 2n = 4x = 40] is a self-pollinated crop. It is a multifaced nutritional food crop with high amounts of proteins (40%), fats (20%), oil contents and as a medicinal crop ( Hymowitz, 1970 ; Singh et al, 2001 ; Rodrigues et al, 2006 ; Medic et al, 2014 ; Rajendran and Lal, 2020 ; Rajendran et al, 2022 ; Ramlal et al, 2022 ). Soybean is a paleopolyploid which has resulted in the presence of more than one copy of a gene in about 75% of its genes and shows differential expression ( Friedrichs et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%